Technology of multilevel prognostic assessment of psychosocial maladjustment in women with depressive disorders as a basis for personification of treatment and rehabilitation approaches in their complex treatment - Isakov , Рустам (Psychosomatic Medicine and General Practice, 2019)
Introduction. A sad sign of today is the tendency to turn depressive disorders into a marker of modern society, the spread of which is steadily growing. Depression makes it difficult to meet basic human needs and negatively affects their daily life, leading to a significant reduction in quality of life and the formation of psychosocial maladjustment (PM), the development and progression of which is influenced by social factors of macro-, meso- and microsocial levels. Of course, such effects of these factors are not the same, and the question of identifying the interaction of maladaptation in the structure of depression, and PM macro-, meso- and microsocial levels have not yet found a final solution, which makes it impossible to develop personalized approaches to treatment and rehabilitation of these patients. Goal. The goal was to develop technology for multilevel prognostic assessment of psychosocial maladaptation in women with depressive disorders, aimed at early detection of the contingent with potentially high levels of maladjustment, as a basis for the personification of treatment and rehabilitation, approaches in their comprehensive treatment. Materials and methods. To achieve this goal, 252 women with depressive disorders were surveyed: 94 people with psychogenic, 83 women with endogenous and 75 patients with organic depression. 48 women had no signs of PD, the other 204 showed manifestations of macro-, meso- and microsocial maladaptation of varying severity. The study was conducted using clinical-psychopathological and psychodiagnostic methods. Results and conclusions. The study proposed a new technology in the form of a scale for estimating the probable degree of macro-, meso- and microsocial maladaptation based on the analysis of the severity of disorders of the depressive, anxiety and obsessive-phobic spectrum - easy to use and suitable for use in health care. I to conduct screening studies to identify early the contingent with potentially high levels of maladaptation, which will allow for the appropriate personification of psychocorrectional and rehabilitation interventions in their comprehensive treatment.